Geographic Variation of Diapause and Sensitive Stages of Photoperiodic Response in Laodelphax striatellus Fallén (Hemiptera: Delphacidae). Issue 1 (2nd February 2016) - Hou, Yang-Yang; Xu, Lan-Zhen; Wu, Yan; Wang, Peng; Shi, Jin-Jian; Zhai, Bao-Ping
Abstract: Large numbers of the small brown planthopper Laodelphax striatellus (Fallén) (Hemiptera: Delphacidae) occur in temperate regions, causing severe losses in rice, wheat, and other economically important crops. The planthoppers enter diapause in the third- or fourth-instar nymph stage, induced by short photoperiods and low temperatures. To investigate the geographic variation in L. striatellus diapause, we compared the incidence of nymphal diapause under various constant temperature (20 and 27°C) and a photoperiod of 4:20, 8:16, 10:14, 12:12, 14:10, and 16:8 (L:D) h regimes among three populations collected from Hanoi (21.02° N, 105.85° E, northern Vietnam), Jiangyan (32.51° N, 120.15° E, eastern China), and Changchun (43.89° N, 125.32° E, north-eastern China). Our results indicated that there were significant geographic variations in the diapause of L. striatellus . When the original latitude of the populations increased, higher diapause incidence and longer critical photoperiod (CP) were exhibited. The CPs of the Jiangyan and Changchun populations were ∼12 hr 30 min and 13 hr at 20°C, and 11 hr and 11 hr 20 min at 27°C, respectively. The second- and third-instar nymphs were at the stage most sensitive to the photoperiod. However, when the fourth- and fifth-instar nymphs were transferred to a long photoperiod, the diapause-inducing effect of the short photoperiod on young instars was almost reversed. The considerable geographic variations in the nymphal diapause of L. striatellus reflect their adaptation in response to a variable environment and provide insights to develop effective pest management strategies.